Unraveling the genetic mysteries of spinal muscular atrophy in Chinese families - Shanshan Gao; Duo Chen; Qianqian Li; Xuechao Zhao; Chen Chen; Lina Liu; Miao Jiang; Zhenhua Zhao; Yanhua Wang; Xiangdong Kong (Orphanet Journal of Rare Diseases)
Abstract Objective Spinal muscular atrophy (SMA) is a motor neuron disorder encompassing 5q and non-5q forms, causing muscle weakness and atrophy due to spinal cord cell degeneration. Understanding its genetic basis is crucial for genetic counseling and personalized treatment options. Methods This study retrospectively analyzed families of patients suspected of SMA at our institution from February 2006 to March 2024. Various molecular techniques, including multiplex ligation-dependent probe amplification analysis, long-range polymerase chain reaction (PCR) combined with nested PCR, Sanger sequencing, and whole-exome sequencing were employed to establish a thorough genetic variant profile in 680 Chinese pedigrees with clinically suspected SMA. Results Out of 680 families suspected of having SMA, 675 exhibited mutations in the SMN1 gene, while three families were linked to mutations in the IGHMBP2 gene. One family exhibited a genetic variation in the NEB gene, and another family exhibited a variation in the SCO2 gene. Among the families with mutations in the SMN1 gene, 645 families exhibited either E7‒E8 or E7 homozygous deletion. Some families displayed E7‒8 heterozygous deletions along with other mutations, such as E1 or E1‒6 heterozygote deletion and point mutations. Furthermore, one family demonstrated a compound-heterozygous double mutation, while another carried a type “2 + 0” mutation alongside a point mutation. Conclusions This study comprehensively analyzed the genetics of suspected familial SMA cases in the Chinese population, providing insights into the molecular genetic mechanisms of SMA and the utility of various detection techniques. The findings revealed important implications for genetic counseling, prenatal diagnosis, and targeted therapies in clinical practice.